Accelerated biological aging as potential mediator in the relationship between central obesity and lung cancer risk - Liu, Hongya; Deng, Zhihao; Gong, Zhongwen; Bai, Yangjiao; Li, Yongjia; Zhou, Qing; Ma, Jian; Gao, Jing; Lian, Xuemei (Frontiers in Aging, 2025)
BackgroundThe increased prevalence of obesity and incidence of lung cancer have raised significant concerns worldwide. However, the relationship between obesity and lung cancer risk, and the potential mediating effect of biological aging remains poorly understood.MethodsUsing UK Biobank database, this population-based cohort study employed multivariable Cox regression to estimate HRs (Hazard Ratios) for obesity indices (waist circumference [WC], waist-hip ratio [WHR], body shape index [ABSI], conicity index [C-Index]) and lung cancer risk. Biological aging was evaluated via PhenoAge and Klemera-Doubal method age (KDMAge), with acceleration calculated by regressing biological on chronological age. Longitudinal mediation analysis explored their mediating effects.ResultsAmong the 301,398 participants in the study, 2,466 incident cases of lung cancer were identified. All central - obesity - related indices were significantly associated with elevated risk of lung cancer, with (WC: HR = 1.10, 95% CI 1.02–1.19; WHR: 1.10, 1.03–1.18; ABSI: 1.73, 1.54–1.94; C-Index: 1.51, 1.35–1.69). Notably, PhenoAge/KDMAge acceleration mediated the associations between WHR, ABSI, C -Index and the lung cancer risk, with mediated proportions from 1.85% to 32.67%.ConclusionThis study highlights central obesity was significantly associated with incident risk of lung cancer, emphasizing biological aging’s mediating role.